Eric Carle's dragons dragons & other creatures that never were - Carle, Eric.; Whipple, Laura (New York : Philomel Books, 1991)
An illustrated collection of poems about dragons and other fantastic creatures by a variety of authors.
Includes indexes.
Elem. School Library Collection
School Library Journal starred
Wilson's Children
6.4
3-6.
Keywords: Animals, Mythical -- Juvenile poetry; Animals, Mythical -- Poetry; Mythical animals -- Poetry; Poetry, English -- Collected works; Poetry, English -- Collected works